Gastric Perforation and Phlegmon Formation by Foreign Body Ingestion - Avila Alvarez, Albert Alejandro; Parra, Jose Fernando; Buitrago, Diego Andres; Rodriguez, Fernando; Moreno, Atilio (Archives of Academic Emergency Medicine, 2014)
This is a case report of foreign body ingestion in a suicide attempt resulting in gastric perforation and phlegmon formation during a subsequent 6 month period that eventually required surgical intervention. The patient had a prolonged course because she did not report a history of foreign body ingestion and the initial evaluating physicians had no suspicion about possible foreign body ingestion and may have missed important findings on physical examination. Gastric perforation by a foreign objectÂ may have a slow course rather than presenting acute abdomen. The realization of a proper physical examination in the emergency department is key to an accurate diagnosis.